Revitalisasi Sektor Pertanian - Martomo, Yitno Puguh (Universitas Surakarta, 2011)
Rapid urban industry development has been perceived as clearly essential if rural labor. Made redundant by the rapid gains in labor productivity in agriculture, is to escape from low productivity employment in the rural sector and make an important contribution to nation economic growth. Argo industry can be defined loosely as certain from of agriculture (live stock, fisheries) production it self. In particular, those which are tending toward an industrial character. Highly commercialized and normally involving significant investment and working capital. The agricultural production unit them selves are not necessary large-scale. Agro based industries on the upstream (input) and downstream (output processing) side of agricultural production (generally limited to the first stage of agro linkedÂ in put production of processing, or at least to relatively immidiate stages). Â Key words: revitalization, agro.